Bacterial spectrum analysis and antimicrobial susceptibility study of osteoradionecrosis of the jaw in Southern China. (6th August 2021) - Zhu, Yue; Liang, Jianfeng; Wang, Fang; Li, Jiaxin; Wang, Cheng; Hou, Jinsong
Abstract: Objective: Osteoradionecrosis of the jaw (ORNJ) is one of the most common and serious complications after radiotherapy of head and neck malignancies due to the high incidence of nasopharyngeal cancer in Southern China. Clinicians lack understanding and consensus on anti‐infective treatment in ORNJ lesions. This research aims to provide evidence for rational use of antibiotics by reviewing the bacterial spectrums and antimicrobial susceptibility test of ORNJ patients. Methods: We collected patient who was diagnosed with ORNJ from November 2012 to June 2019 in our hospital. Exudate or bone unexposed wound surface sampling, agar plates culturing, and susceptibility testing were analyzed. Descriptive statistics were used for data presentation. Results: A total of 219 samples were collected in our retrospective study. The most common cultured bacteria were Klebsiella pneumoniae (15.10%), Pseudomonas aeruginosa (13.54%), and Staphylococcus aureus (10.94%). Methicillin‐resistant Staphylococcus aureus (MRSA) accounted for 5.21% in the whole positive samples. Ticarcillin, Ofloxacin, Vancomycin, Tigecycline, and Meropenem were more susceptible than other antibiotics to treat uncontrollable infection. Conclusions: Our research provided objective evidence for understanding the types of local bacterial flora and drug susceptibility in ORNJ lesions and gave a guiding reference for empirical antibiotics medication.